2024
DOI: 10.1039/d3fo01235b
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene alleviates abdominal aortic aneurysm via inhibiting macrophage pyroptosis by activating the miR-146a-5p/TRAF6 axis

Huoying Cai,
Lin Huang,
Mingshan Wang
et al.

Abstract: Our findings provide evidence that macrophage pyroptosis contributes to the development of AAA and that the activation of the miR-146a/TRAF6 axis by pterostilbene protects against macrophage pyroptosis and AAA formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In recent years, non-coding RNAs, especially lncRNAs and miRNAs, have been considered as gene expression regulators. A prior study reported that miR-146a-5P could inhibit macrophage pyroptosis and alleviate AAA [ 56 ]. Other studies reported that lncRNA FGD-AS1 could promote AAA occurrence by targeting miR-195-5P in vascular smooth muscle cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, non-coding RNAs, especially lncRNAs and miRNAs, have been considered as gene expression regulators. A prior study reported that miR-146a-5P could inhibit macrophage pyroptosis and alleviate AAA [ 56 ]. Other studies reported that lncRNA FGD-AS1 could promote AAA occurrence by targeting miR-195-5P in vascular smooth muscle cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%